ANALISIS SISTEM PENGELOLAAN KEUANGAN MANUAL DALAM MENINGKATKAN EFISIENSI OPERASIONAL PADA PT HAYYU PRATAMA DEALER - Raisya Anjar Nurhidayah; Khairil Anwar (Jurnal Salome : Multidisipliner Keilmuan, 2025)
This study analyses the manual financial management system implemented at PT Hayyu Pratama Dealer and its impact on the company's operational efficiency. The study uses a qualitative descriptive approach with data collection methods through direct interviews with financial staff and documentation related to the company's financial administration processes. The results show that transaction recording is still done manually using Microsoft Excel, which requires high accuracy and considerable time. The verification process is carried out in layers to ensure accuracy, but on the other hand, it slows down the administrative process. The biggest challenges faced are the risk of input errors, incomplete transaction evidence from vendors, and increased workload when transaction volumes are high. This study recommends the use of a digital financial system to improve efficiency, accuracy, and reporting speed. Overall, financial digitalisation is considered a strategic step to improve the company's operational effectiveness and competitiveness.